Characterization of the ultrashort‐TE (UTE) MR collagen signal†. (13th August 2015) - Siu, Adrienne G.; Ramadeen, Andrew; Hu, Xudong; Morikawa, Lily; Zhang, Li; Lau, Justin Y. C.; Liu, Garry; Pop, Mihaela; Connelly, Kim A.; Dorian, Paul; Wright, Graham A.
<x xml:space="preserve">Abstract</x> Although current cardiovascular MR (CMR) techniques for the detection of myocardial fibrosis have shown promise, they nevertheless depend on gadolinium‐based contrast agents and are not specific to collagen. In particular, the diagnosis of diffuse myocardial fibrosis, a precursor of heart failure, would benefit from a non‐invasive imaging technique that can detect collagen directly. Such a method could potentially replace the need for endomyocardial biopsy, the gold standard for the diagnosis of the disease. The objective of this study was to measure the MR properties of collagen using ultrashort TE (UTE), a technique that can detect short T2* species. Experiments were performed in collagen solutions. Via a model of bi‐exponential T2* with oscillation, a linear relationship (slope = 0.40 ± 0.01, R2 = 0.99696) was determined between the UTE collagen signal fraction associated with these properties and the measured collagen concentration in solution. The UTE signal of protons in the collagen molecule was characterized as having a mean T2* of 0.75 ± 0.05 ms and a mean chemical shift of −3.56 ± 0.01 ppm relative to water at 7 T. The results indicated that collagen can be detected and quantified using UTE. A knowledge of the collagen signal properties could potentially be beneficial for the endogenous detection of myocardial fibrosis. Copyright © 2015 John Wiley & Sons, Ltd.